2020
DOI: 10.1093/mnras/staa476
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray and radio activity of typical and luminous Ly α emitters from z ∼ 2 to z ∼ 6: evidence for a diverse, evolving population

Abstract: Despite recent progress in understanding Lyα emitters (LAEs), relatively little is known regarding their typical black hole activity across cosmic time. Here, we study the X-ray and radio properties of ∼4000 LAEs at 2.2 < z < 6 from the SC4K survey in the COSMOS field. By exploring deep Chandra Legacy data, we reach an X-ray luminosity of ∼ 10 42.4 erg s −1 for the deepest, full sample stack of ∼480 Ms. We detect 254 (6.8% ± 0.4%) of the LAEs individually in the X-rays (S/N>3) and find an average luminosity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 133 publications
(263 reference statements)
6
27
3
Order By: Relevance
“…Further support to this picture is provided by the tomographic analysis of the high-z Lyα LF in the COSMOS field performed by Sobral et al (2018b) by using a combination of optical, infrared and X-Ray data. In their work, the major contribution to the LF at L Lyα 10 43 is provided by sources showing X-Ray loud counterparts, thus likely to be AGN (see also e.g., Matthee et al 2017b;Calhau et al 2020). Their work shows how this contribution completely vanishes at z 3.5, thus paralleling the peak of AGN activity usually observed at z ∼ 2 − 3 (e.g., Hasinger et al 2005;Miyaji et al 2015).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Further support to this picture is provided by the tomographic analysis of the high-z Lyα LF in the COSMOS field performed by Sobral et al (2018b) by using a combination of optical, infrared and X-Ray data. In their work, the major contribution to the LF at L Lyα 10 43 is provided by sources showing X-Ray loud counterparts, thus likely to be AGN (see also e.g., Matthee et al 2017b;Calhau et al 2020). Their work shows how this contribution completely vanishes at z 3.5, thus paralleling the peak of AGN activity usually observed at z ∼ 2 − 3 (e.g., Hasinger et al 2005;Miyaji et al 2015).…”
Section: Introductionmentioning
confidence: 83%
“…Recent compelling hints point towards identifying the majority of high-z Lyα-emitting sources at L Lyα > 2 × 10 43 erg s −1 as AGN/QSOs (see e.g., Nilsson et al 2011;Konno et al 2016;Matthee et al 2017b;Sobral et al 2018a,b;Calhau et al 2020). The work of Sobral et al (2018a), in particular, pointed out the co-existence of two different classes of luminous z ∼ 2 − 3 LAEs at roughly 3 L * , namely dust-free, highly star-forming galaxies and AGN.…”
Section: Agn/qsos or Star-forming Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We can estimate the extent of this obscuration by comparing the derived properties of the AGN to similar quasars at these redshifts. Calhau et al (2020) studied the radio and X-ray properties of ∼4000 LAEs in the COSMOS SC4K field over 2 < z < 6 and found a correlation between the hardness ratio, which determines the level of obscuration, and the X-ray luminosity of X-ray detected LAEs, with the more luminous X-ray LAEs being observed to have smaller hardness ratios. Our estimate for the intrinsic X-ray luminosity of COLA-1 places it above the hardness 0 category when compared to the Calhau et al (2020) sample, with properties similar to those of obscured AGN discovered in the COSMOS field by Marchesi et al (2016).…”
Section: Obscuration Of the Agnmentioning
confidence: 99%
“…Calhau et al (2020) studied the radio and X-ray properties of ∼4000 LAEs in the COSMOS SC4K field over 2 < z < 6 and found a correlation between the hardness ratio, which determines the level of obscuration, and the X-ray luminosity of X-ray detected LAEs, with the more luminous X-ray LAEs being observed to have smaller hardness ratios. Our estimate for the intrinsic X-ray luminosity of COLA-1 places it above the hardness 0 category when compared to the Calhau et al (2020) sample, with properties similar to those of obscured AGN discovered in the COSMOS field by Marchesi et al (2016). It was found that for AGN having log L X /ergs s −1 > 44.1 in the 2-10 keV range, obscured sources are two to three times as abundant as unobscured ones at z ∼ 6−6.5 (Marchesi et al 2016).…”
Section: Obscuration Of the Agnmentioning
confidence: 99%